Highlights of New Strategies to Increase the Efficacy of Transition Metal Complexes for Cancer Treatments - Ester Giorgi; Francesca Binacchi; Carlo Marotta; Damiano Cirri; Chiara Gabbiani; Alessandro Pratesi (Molecules, 2022)
Although important progress has been made, cancer still remains a complex disease to treat. Serious side effects, the insurgence of resistance and poor selectivity are some of the problems associated with the classical metal-based anti-cancer therapies currently in clinical use. New treatment approaches are still needed to increase cancer patient survival without cancer recurrence. Herein, we reviewed two promising—at least in our opinion—new strategies to increase the efficacy of transition metal-based complexes. First, we considered the possibility of assembling two biologically active fragments containing different metal centres into the same molecule, thus obtaining a heterobimetallic complex. A critical comparison with the monometallic counterparts was done. The reviewed literature has been divided into two groups: the case of platinum; the case of gold. Secondly, the conjugation of metal-based complexes to a targeting moiety was discussed. Particularly, we highlighted some interesting examples of compounds targeting cancer cell organelles according to a third-order targeting approach, and complexes targeting the whole cancer cell, according to a second-order targeting strategy.